Smoking, COPD, Infection, and Lung Cancer: How are They Interconnected? - Tanuwihardja, Benjamin J. (PT Dexa Medica, 2020)
A case of an elderly ex-smoker chronic obstructive pulmonary disease (COPD) patient with controlled type 2 diabetes mellitus (T2DM) as comorbid was followed-up for 10 years. His stable COPD in the course of time slowly declined to multiple acute exacerbation (AE)-COPD and multiple hospital admissions. High-dose systemic corticosteroids given during AE-COPD with prolonged oral steroids continuation led to depressed immunity that ended with severe immunosuppression, causing sepsis and chronic heart failure (CHF) with non-ST elevated myocardial infarction (NSTEMI) and worsening of COPD in his ninth year follow-up. This immunosuppression also triggered the emergence of lung cancer by allowing malignant cell to evade immune surveillance. Fortunately patient is survived and recovered to stable COPD.